(untitled) (Applied Biological Research, 2023)
The present study was aimed to evaluate the efficacy of some oil cake extracts as seed priming agent and nutrient source to improve the seed quality attributes. Studies were conducted on green gram cv. ‘CO 8’ to identify the suitable oil cake extracts and optimize the concentration of oil cake extracts for seed priming. The extracts of oil cakes viz., groundnut, sesame, coconut, cotton and neem were evaluated using variable concentrations i.e. 5, 10, 15 and 20%. The seeds primed with oil cake extracts increased seed quality attributes viz., speed of germination, germination percentage, root and shoot length, dry matter production and vigour index as compared to the hydro- and non-primed seeds. The extract of coconut oil cake (15%) was identified as the best suitable seed priming agent for green gram.